Inside Cover Image, Volume 6, Issue 2. (March 2017) - Stower, Matthew J.; Bertocchini, Federica
Abstract : The inside cover image, by Matthew J. Stower and Federica Bertocchini, is based on the Advanced Review The Evolution of amniote gastrulation: the blastopore‐primitive streak transition, DOI:10.1002/wdev.262 . Abstract : The inside cover image, by Matthew J. Stower and Federica Bertocchini, is based on the Advanced Review The Evolution of amniote gastrulation: the blastopore‐primitive streak transition, DOI:10.1002/wdev.262 .